DEHIDRATASI VIRGIN COCONUT OIL DENGAN SODA ASH UNTUK MEMENUHI STANDAR NASIONAL INDONESIA PADA KELOMPOK TANI BINA WARGA 1 DESA PANCANEGARA KECAMATAN PABUARAN KABUPATEN SERANG - Sri Sulasminingsih; Budiman Adi Setyawan; Lomo Mula Tua (Bina Teknika, 2017)
The identification of Virgin Coconut Oils (VCO) components had been done from Kelompok Tani Bina Warga 1 Desa Pancanegara productions.The identifications had been done especially to isolated method with natrium carbonate added , that is called with the dehydrated proses .   VCO analysis of physical properties like density and organoleptic test, standard of benefit value correlation with composition of essensial fatty acids and standard of endurance levels like  water and free fatty acids content. The Result of this identifications that inducement isolation methode provided 0,130 litre/kg  of  VCO, colourless , deliciously and fragrant cocont oily,density 0,925 (g/ml), water content  0,19%, free fatty acids 0,10%. Fatty acids composition those are lauric 39,0 % (45,1-53,2 %), myristic 17,8 % (16,8-21 %), palmitic 8,7 % (5,0-10,0 %). The result of this identification appropriate with SNI 7381:2008 and Asian and Pacific Coconut Community (APCC) are still below.